Assistance in Creating Google Sites as a Marketing Platform for Anwarul Quran Islamic Boarding School - Sofyan, Syaakir; Noval; Fatma; Ela Agustina; Khusnul Khatimah; Zahra (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2025)
This community service program aims to enhance the digital skills of students and administrators at Pondok Pesantren Anwarul Quran in creating and managing websites using Google Sites. In today’s digital era, educational institutions, including Islamic boarding schools (pesantren), require an online platform to disseminate information and manage administration more effectively. A well-designed website enables pesantren to promote its educational programs, document activities, and improve communication with a broader audience. The methods used in this program include direct training, practical mentoring, and continuous evaluation. Participants were introduced to the basics of website development using Google Sites, hands-on website creation, and strategies for independently managing and updating content. The results of this program show that students and administrators have acquired fundamental skills in website development and management. Consequently, pesantren can enhance its online presence and strengthen its visibility in the digital world. The success of this initiative demonstrates that similar programs can be implemented in other pesantren to support digital transformation in faith-based education.